Predictive value of Manchester Triage System: evaluation of patients' clinical outcomes - Guedes, Helisamara Mota (2015)
Objective: to analyze the predictive value of the Manchester Triage System in relation to clinical outcome of patients. Methods: prospective observational study of 577 patients admitted to the ER and subjected to risk classifi cation. The Therapeutic Intervention Scoring System-28 (TISS-28) was used to measure the severity of patients (primary outcome) and secondary outcomes: high / transfer, death, and length of hospital stay. Descriptive and univariate analyzes were conducted. Results: patients classifi ed as red are 10.7 times more likely to have scores above 14 in TISS-28 in relation to others. Patients classifyed as red have 5.9 times more chance of progression to death compared to others. Patients of high priority service are 1.5 times more likely to be hospitalized over fi ve days than low priority. Conclusion: STM proved a good predictor of clinical outcomes.